Meningkatkan Kemampuan Menulis dan Membaca Siswa Tunanetra Melalui Puzzle Braille - Fahryzal Oktova Anggara Styaputra; Umi Safiul Ummah (Department of Special Education, 2015)
The Development of Braille Puzzle Media for Increasing The Ability of Reading and Writing for Children With Visual Impairment of 4th Grade In Elementary Special Education.The purpose of this research is developping a media that can be used to increase the reading and writing ability ofchild with visual impairment on fourth grade in elementary special education. This research was adapted by steps of Sugiyono’s model consisting of eight steps. The result of media experts 88% , matter experts 90%, practicy experts 82%, small group testing 82%. So this product braille puzzle otherwise very worthy to be used.Tujuan pengembangan ini adalah menghasilkan sebuah media sebagai sarana melatih kemampuan membaca dan menulis siswa tunanetra. Penelitian ini mengadaptasi langkah-langkah pengembangan dari Sugiyono yaitu terdiri dari 8 tahap. Hasil penilaian ahli media 88%, ahli materi 90%, ahli praktisi 82%, dan hasil uji coba kelompok kecil82%. Dengan itu produk puzzle braille dinyatakan sangat layak digunakan.